2020
DOI: 10.1002/cssc.201903293
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Iron‐ and Nitrogen‐Codoped Carbon Nanotubes from Waste Plastics Pyrolysis for the Oxygen Reduction Reaction

Abstract: A novel method for the preparation of iron‐ and nitrogen‐codoped carbon nanotubes (Fe‐N‐CNTs) is proposed, based on the catalytic pyrolysis of waste plastics. First, carbon nanotubes are produced from pyrolysis of plastic waste over Fe‐Al2O3; then, Fe‐CNTs and melamine are heated together in an inert atmosphere. Different co‐pyrolysis temperatures are tested to optimize the electrocatalyst production. A high doping temperature improves the degree of graphite formation and promotes the conversion of nitrogen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Copyright (2014) with permission from Elsevier improved electrocatalytic activity for CNTs produced at higher catalyst temperature, but there was little difference in performance for the CNTs produced from different types of waste plastic. Cai et al [136] have reported on a novel route to produce nitrogen and iron carbon nanotubes with an application as electro-catalysts for the oxygen reduction reaction in fuel cells or metal air batteries. Fe-CNTs were produced from the pyrolysis-catalysis of polypropylene with a Fe-Al 2 O 3 catalyst, followed by co-pyrolysis of the Fe-CNTs with melamine.…”
Section: Application Of Carbon Nanotubes Produced From Waste Plasticsmentioning
confidence: 99%
“…Copyright (2014) with permission from Elsevier improved electrocatalytic activity for CNTs produced at higher catalyst temperature, but there was little difference in performance for the CNTs produced from different types of waste plastic. Cai et al [136] have reported on a novel route to produce nitrogen and iron carbon nanotubes with an application as electro-catalysts for the oxygen reduction reaction in fuel cells or metal air batteries. Fe-CNTs were produced from the pyrolysis-catalysis of polypropylene with a Fe-Al 2 O 3 catalyst, followed by co-pyrolysis of the Fe-CNTs with melamine.…”
Section: Application Of Carbon Nanotubes Produced From Waste Plasticsmentioning
confidence: 99%
“…Through XPS analysis, an obvious difference in the nitrogen species was observed for varying nitrogen‐doping temperatures (Figure 3G) [52] . Between the temperature range of 700 °C and 800 °C nitride‐like species were formed mainly due to the evolution of g‐CN x during the thermal degradation of nitrogen precursor [52,98] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, carbon is also employed as a support for the PGM‐based electrocatalysts which makes carbon support an essential research theme for ORR applications [48] . Carbon‐based ORR electrocatalysts can be fabricated through the valorization of plastic waste in a facile and cost‐effective way [49–52] . Hence, both ineffective waste management and energy crisis can be addressed simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations